Examining cross-cultural validity of the socio-emotional wealth (SEW) construct: Case of Moroccan family firms (Economic and Political Thought, 2021)
The concept of socio-emotional wealth (SEW) is gaining popularity among the scientific community as the potential dominant paradigm in the family business domain. However this ‘’new homegrown’’ theoretical approach still holds several ambiguities that need addressing, for instance, the absence of clear consensual measures, uncertainty regarding the cross-cultural validity of the SEW perspective, and so forth. Nevertheless, this paper represents multiple case study research that seeks to verify the validity of the SEW approach in the context of Morocco. The results obtained reflect various contextual particularities that will contribute to the improvement and the advancement of the socio-emotional wealth paradigm.
Keywords: socio-emotional wealth (SEW), cross-cultural, family business